Mechanical properties of lightweight mortar modified with oil palm fruit fibre and tire crumb - Abd. Aziz, Farah Nora Aznieta; Mohammed Bida, Sani; Mohd. Nasir, Noor Azline; Jaafar, Mohd Saleh (Elsevier, 2014)
This research use oil palm fruit fibre (OPFF) as a greener and more cost-effective approach to improve the tire crumb mortar composite strengths. The mechanical properties of tire crumb and oil palm fruit fibre lightweight mortar with addition of 0%, 0.5%, 1% and 1.5% OPFF and tire-crumb replacement of 0–40% by volume of aggregate were studied. The composite mixtures were subjected to the compression, split tensile and flexural tests. The addition of 0.5% OPFF to the composite was found to improve the compressive strength, split tensile strength and flexural strength of the mortar composites.